The effect of the color of the rearing container on the growth and survival of tambaqui (Colossoma macropomum) - Andrian Fikri; Suri Purnama Febri; Siti Komariyah; Cici Maulida; Ika Rezvani Aprita; Suraiya Nazlia; Febby Hadi Setyawan; Ahyar Pulungan; Devita Aristya Sri Widya (Jurnal Perikanan Terpadu, 2025)
Tambaqui (Colossoma macropomum) is a commodity with high economic value because it is a consumption fish. The purpose of this study was to analyze the effect of different colors of rearing containers on the growth and survival of freshwater pomfret fry. The method used in this study was an experimental method with 4 treatments repeated 3 times. In each treatment, a different color was given: P1 = transparent (control), P2 = black, P3 = blue, P4 = green. The results of these treatments significantly affected absolute weight growth, absolute length growth, and daily growth rate. Meanwhile, the survival rate and feed conversion ratio did not have a significant difference. The highest absolute weight growth was found in P3 at 13,67g, while the lowest absolute weight growth was found in P1 at 8,75g. The highest absolute length growth was found in P3 at 3,49cm, while the lowest absolute length growth was found in P1 at 2,39cm. Meanwhile, the highest daily growth rate was found in P3 at 34,18g, while the lowest daily growth rate was found in P1 at 21,88g. From the results of providing different container colors in the maintenance container, the brighter the color used, the better the resulting growth is categorized